Developmental potential and kinetics of pig embryos with different cytoplasmic volume. Issue 2 (15th November 2013) - Li, Juan; Li, Rong; Villemoes, Klaus; Liu, Ying; Purup, Stig; Callesen, Henrik
Summary: The effects of cytoplasmic volumes on development and developmental kinetics of in vitro produced porcine embryos were investigated. During hand-made cloning (HMC), selected cytoplasts were separated into two groups according to their size in relation to the initial oocyte: ~75% or ~50%. Following two fusion steps and activation (day 0), reconstructed embryos were cultured in vitro for 6 days. Cleavage rates on day 2 as well as blastocyst rates and cell numbers on day 6 were recorded. Results showed that embryo development was no different for ~50% versus ~75% cytoplasm at first fusion. This result was used in the following experiments, where the effect of varying cytoplasm volume in second fusion to obtain a final cytoplasm volume of ~75% to ~200% was tested. The results showed that the lowest quality was obtained when the final cytoplasm volume was ~75% and the highest quality at ~200% of the original oocyte. Similar results were observed in parthenogenetic (PA) embryos activated with different cytoplasmic volumes. A common pattern for the developmental kinetics of HMC and PA embryos was observed: the smaller group tended to have a longer time for the first two cell cycles, but subsequently a shorter time to form morula and blastocyst. In conclusion, the developmental kinetics of in vitro produced embryos was affected by the cytoplasm volume of the initial oocyte, and this further accounted for the developmental ability of the reconstructed embryos.